Analysis of Students' learning of computer programming in a computer laboratory context. (3rd September 2019) - Thuné, Michael; Eckerdal, Anna
ABSTRACT: Previous research shows that many students find it difficult to learn computer programming. To learn computer programming includes both gaining theoretical understanding and learning to develop programmes in practice. To this end, teachers commonly design programming exercises for the students in the computer laboratory. To be able to improve the process of designing such exercises, there is a need of a more detailed understanding of the interaction between learning of theory and learning of practice in laboratory sessions. In this paper, an approach for investigating this interaction is proposed. Theoretically, the approach is based on phenomenography and variation theory. To illustrate the approach, it is demonstrated in detail how it was applied to a small but rich case of empirical data from a computer laboratory session. The main result presented here is the new approach for analysing data. In addition, the results of the case study shed preliminary light on the interaction between learning of practice and learning of theory when students work with programming assignments in the laboratory.